2019
DOI: 10.1007/s00213-019-05421-x
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine enhances auditory processing in healthy and normal-hearing young adult nonsmokers

Abstract: Rationale Electrophysiological studies show that systemic nicotine narrows frequency receptive fields and increases gain in neural responses to characteristic frequency stimuli. We postulated that nicotine enhances related auditory processing in humans. Objectives The main hypothesis was that nicotine improves auditory performance. A secondary hypothesis was that the degree of nicotine-induced improvement depends on the individual's baseline performance. Methods Young (18-27 years old), normal-hearing nonsmoke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 38 publications
0
18
0
3
Order By: Relevance
“…Moreover, the nicotine effect may depend on the task. Pham et al 12 found that nicotine improved performance for auditory selective attention and tone-innoise detection but not for easier temporal or spectral resolution tasks. Similar to the previous studies, the present study found a signi cant nicotine effect on intensity discrimination but not on frequency-related tasks (see Limitations and Future Directions later).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the nicotine effect may depend on the task. Pham et al 12 found that nicotine improved performance for auditory selective attention and tone-innoise detection but not for easier temporal or spectral resolution tasks. Similar to the previous studies, the present study found a signi cant nicotine effect on intensity discrimination but not on frequency-related tasks (see Limitations and Future Directions later).…”
Section: Discussionmentioning
confidence: 99%
“…All procedures leading up to experiments, including method of drug delivery and time between sessions to allow for drug clearance followed those speci ed by Pham et al 12 . Brie y, six mg of nicotine was delivered in the form of two pieces of mint-avored polacrilex gum (4 mg and 2 mg; Nicorette®, Johnson & Johnson, Inc).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because activity in the PMT is influenced by the sleep-wake cycle, attention, rewards, and sensory novelty, it is hypothesized that PMT neurons regulate auditory processing in the IC as a function of behavioral state (Jones, 1991;Kozak et al, 2005;Schofield et al, 2011;Boucetta et al, 2014). Consistent with this, in vivo studies have shown that nicotinic drugs alter the gain of input-output functions in IC neurons (Farley et al, 1983;Habbicht & Vater, 1996), and human psychophysics studies indicate that nicotine improves performance in auditory attention and discrimination tasks (Knott et al, 2012;Smucny et al, 2016;Pham et al, 2020), an effect partly attributable to alterations in the IC (Askew et al, 2017). In addition, temporal coding of auditory stimuli is degraded in the IC of α7 knockout mice (Felix et al, 2019).…”
Section: Introductionmentioning
confidence: 95%
“…Previous studies have identified clear roles for muscarinic signaling in the IC, including roles in cortically driven plasticity (Ji et al, 2001;Ji & Suga, 2009) and stimulus specific adaptation (Ayala & Malmierca, 2015), but the roles of nicotinic signaling in the IC are less clear. Psychophysical studies indicate that systemic nicotine exposure in non-smokers can enhance performance in auditory tasks (Harkrider & Hedrick, 2005;Knott et al, 2009;Pham et al, 2020). Intriguingly, recent work from Askew and colleagues suggests that systemic nicotine sharpens frequency tuning in the IC, which likely contributes to sharper tuning in auditory cortex and improved discrimination in behavioral tasks (Askew et al, 2017).…”
Section: Functional Implications For Auditory Processingmentioning
confidence: 99%